Evaluation of Clinical and Ultrasound Changes With the Use of Microneedling Versus Fractional CO2 Laser in Atrophic Acne Scars - Claudio Ñanco Meléndez; Mathias Yagnam; Marco Muñoz; Javier Contador; Walter Gubelin; Fernando Chicao; Jerry Tan; Ximena Wortsman (Mattioli1885, 2024)
Introduction: Atrophic acne scarring, a common sequela of acne, can be treated by different interventions, including microneedling and laser resurfacing. Objectives: We sought to evaluate the comparative efficacy of microneedling versus fractional CO2 laser in treating atrophic acne facial scars using clinical outcomes and imaging with high and ultra-high frequency ultrasound. Methods: Participants received 2 sessions, separated by 1 month, of microneedling on the left side of the face and fractional CO2 laser on the right. Clinical and color Doppler ultrasound evaluations (24 and 70 MHz) were conducted at baseline and 3 months after treatment. Each patient completed questionnaires on satisfaction, pain, and adverse effects. Results: Nine subjects were enrolled. The frequency order of scar types was boxcar, ice pick, and rolling. At 3 months, a decrease in scar scores was observed for total scars using ECCA scale (p= 0,0005), ice pick scars (p= 0.0128), and rolling scars (p= 0.0007). Both treatments were rated as good or very good by patient assessments. There was a low frequency of pain and hyperpigmentation reported with both modalities, albeit somewhat higher with microneedling. Twenty-two scars analyzed by ultrasound demonstrated a trend to decrease in size; however, no significant changes were observed for either microneedling or CO2 laser treatments. Moreover, there were no significant differences between these methods. Conclusion: Both microneedling and CO2 laser improved atrophic acne scars. Ultrasound did not show significant differences between these modalities.